2022
DOI: 10.3389/fendo.2022.1002583
|View full text |Cite
|
Sign up to set email alerts
|

Daily requirement of softgel thyroxine is independent from gastric juice pH

Abstract: BackgroundSoftgel levothyroxine (LT4) preparation showed a better in vitro dissolution profile at increasing pH as compared to tablet LT4 preparation. Clinical studies suggested a better performance of softgel LT4 preparation in patients with gastric disorders but whether this finding is related to gastric juice pH variation in vivo is not known.MethodsTwenty-eight hypothyroid patients (24F/4M; median age=50 treated with tablet LT4 (median dose= 1.65 µg/kg/day) and with stable thyroid stimulating hormone (TSH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…These data were confirmed in patients with impaired gastric acidic output ( 15 ). Recently, the independence of the LT4-C requirement on gastric juice pH in vivo has been shown ( 9 ). In the present study, the better performance of LT4-C compared to the tablet preparation is evident, even after excluding patients with known features interfering with thyroxine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were confirmed in patients with impaired gastric acidic output ( 15 ). Recently, the independence of the LT4-C requirement on gastric juice pH in vivo has been shown ( 9 ). In the present study, the better performance of LT4-C compared to the tablet preparation is evident, even after excluding patients with known features interfering with thyroxine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While tablet preparation requires a disintegration/dissolution process to release the active ingredient in the stomach, the liquid solution does not require specific steps, and capsules are rapidly melted in the gastric lumen (5)(6)(7). This means that while the performance of LT4-T closely depends on the characteristic of the gastric environment, the pharmacokinetics of liquid and cap preparations are less likely to be impaired by gastric status (8,9). Several studies demonstrated that LT4-T efficacy can be reduced by food intake, medications and gastric disorders influencing gastric pH, thus decreasing LT4 bioavailability (i.e., Helicobacter pylori gastritis, atrophic gastritis, proton-pump inhibitors, aluminium-containing antacids, calcium carbonate, sucralfate, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Following the switch from tablet to soft capsule in 28 patients with hypothyroidism on stable LT4 tablet doses, the LT4 requirement was the same in all 17 patients with normal gastric pH (median pH: 1.52), while in patients with high gastric pH (median pH: 5.02), the requirement for LT4 soft capsules was significantly reduced in 10 out of 11 patients. 15 …”
Section: Introductionmentioning
confidence: 99%